الاستثمار الأجنبي المباشر ودوره في تنافسية الاقتصاد الجزائري - بلقــــــــــاسم, لعـــــــــويـنـي; ربيع, بن عبد الحميـد; شعــيــــــــب, لبــــيـــهــــــــــي (University of eloued جامعة الوادي, 2021)
جاءت هذه الدراسة للتعرف على المجهودات التي تبذلها الجزائر لاستقطاب الاستثمار الأجنبي مباشرة لها، ومعالجة الإشكالية المطروحة والمتمثلة في: " فيما يتمثل الدور الذي يلعبه الاستثمار الأجنبي المباشر في تنافسية الاقتصاد الجزائري؟"، وقد هدفت الدراسة إلى دراسة أساليب جذب الاستثمار الأجنبي المباشر وتوطينه في الجزائر، وتسليط الضوء على المنظومة التشريعية الجزائرية ومختلف التطورات الحاصلة بها لتشجيع الاستثمار الأجنبي المباشر واستقطابه، وتبرز أهمية البحث في التعرف على الاستثمارات الأجنبية المباشرة باعتبارها أداة أساسية في ترقية تنافسية الاقتصاد الوطني، كما تبرز أهميته في أن الاستثمار الأجنبي المباشر يعد الوسيلة الأنجع في تغطية العجز التمويلي للاقتصاد الوطني، وهو من يمكن الاقتصاد الوطني من الرفع من قدرته التنافسية على المستوى الدولي، وقد اعتمدنا المنهج التاريخي من خلال الحديث عن تطور الاستثمارات الأجنبية المباشرة وإبراز أهم المؤشرات عبر سنوات مختلفة، بالإضافة إلى المنهج الوصفي التحليلي لتشخيص وتحليل وتفسير أثر الاستثمار الأجنبي المباشر على تنافسية الاقتصاد الجزائري، وقد توصنا في نهاية الدراسة إلى نتائج أهمها يعتبر الاستثمار الأجنبي المباشر وسيلة الدول النامية في الحصول على مصادر تمويل دولية بديل عن المديونية وعبئها على البلاد، يلعب الاستثمار الأجنبي المباشر دورا إيجابيا في الرفع من تنافسية الاقتصاد الوطني الجزائري من خلال تحسين مؤشرات الاقتصاد الكلي.This study came to identify the efforts made by Algeria to attract foreign investment directly to it, and to address the problem posed in : "What is the role played by foreign direct investment in the competitiveness of the Algerian economy ?", The study aimed to study the methods of attracting foreign direct investment and its settlement in Algeria. shedding light on the Algerian legislative system and the various developments taking place in it to encourage and attract foreign direct investment, and highlight the importance of research in identifying foreign direct investment as an essential tool in promoting the competitiveness of the national economy, and its importance in that foreign direct investment is the most effective way to cover the financing deficit of the national economy, which enables the national economy to increase its competitiveness at the international level. We have adopted the historical approach by talking about the development of foreign direct investments and highlighting the most important indicators over different years, in addition to the descriptive analytical approach to diagnose, analyze and explain the impact of foreign direct investment on the competitiveness of Algerian economy. At the end of the study, we concluded that The most important results are that foreign direct investment is a means for developing countries to obtain international sources of financing as an alternative to indebtedness and its burden on the country. Foreign direct investment plays a positive role in raising the competitiveness of the Algerian national economy by improving macroeconomic indicators.
مذكرة ماستر تجارة دولية
Keywords: الاستثمار الأجنبي المباشر، التنافسية الاقتصادية; foreign direct investment, Economic competitiveness